202k views
4 votes
- (x + 3) - 3x simplify use distributive property

User Kireol
by
4.3k points

2 Answers

5 votes

Answer: -4x - 3

Explanation:

To simplify this expression, distribute the minus first.

- (x + 3) - 3x

-x - 3 - 3x

Now, combine the like terms.

-x - 3x - 3

-4x - 3

User AbhinavD
by
4.4k points
1 vote

Answer:

-4x- 3

Explanation:

Simplify:

Distributive property: a*(b +c) = (a*b) + (a*c)

(-1) is distributed to each term of (x +3).

-(x + 3) - 3x = (-1) *x + 3*(-1) - 3x

= -x - 3 - 3x

= -x - 3x - 3

= -4x - 3

User Gopu
by
4.6k points